Safety and efficacy of tislelizumab plus chemotherapy versus chemotherapy alone as neoadjuvant treatment for patients with locally advanced gastric cancer: real-world experience with a consecutive patient cohort - Jiang, Qi; Liu, Weizhen; Zeng, Xiangyu; Zhang, Chenggang; Du, Yuqiang; Zeng, Liwu; Yin, Yuping; Fan, Jun; Yang, Ming; Tao, Kaixiong; Zhang, Peng (Frontiers in Immunology, 2023)
Objectives: Immunotherapy plus chemotherapy has recently been applied in the neoadjuvant treatment for locally advanced gastric cancer (LAGC), while its superiority over neoadjuvant chemotherapy (NACT) alone remains to be explored. This study explored the safety and efficacy of NACT plus tislelizumab in patients with LAGC. Methods: The data on patients with LAGC who received NACT combined with radical gastrectomy and NACT plus tislelizumab followed by radical gastrectomy was retrospectively collected. Clinicopathological characteristics of the two groups were compared. Results: A total of 119 and 50 patients with gastric cancer treated with NACT and NACT plus tislelizumab, respectively, were enrolled. No significant difference was found between the baseline data of the two groups. The operative time (210.5±70.4 min vs. 237.6±68.4 min, P=0.732), intraoperative blood loss (157.8±75.9 ml vs. 149.1±92.5 ml, P=0.609), and number of dissected lymph nodes (24.7±9.3 vs. 28.1±10.3, P=0.195) was not statistically different between the two groups. In comparison to the NACT plus tislelizumab group, the R0 resection rate (100% vs. 89.9%, P=0.019) and pathologic complete response rate (26.0% vs. 3.4%, P<0.001) were significantly lower in the NACT group. The postoperative complication rates were 24.4% and 26.0% in the NACT and NACT plus tislelizumab groups with no significant difference (P=0.823). In subgroup analysis, tumor regression grade (TRG) (TRG 3: 72.3% vs. 23.5%, P<0.001) and ypN stage (stages 2–3: 46.8% vs. 5.9%, P=0.003) in the NACT group were significantly higher compared with the NACT plus tislelizumab group in esophagogastric junction carcinoma. Conclusion: Compared with the SOX or FOLFOX NACT regimen, NACT plus tislelizumab significantly improved the efficacy and R0 resection rate of LAGC without increasing the incidence of perioperative complications, particularly in esophagogastric junction carcinoma.